Associations between pre- and postnatal maternal stress and cerebral morphology in 5-year-old children utilizing brain growth charts - Paavola, Iida-Maria (My University, 2026)
Background: Maternal stress affects the development of offspring brain development, leadin to possible structural and behavioral outcomes. Stress can occur as anxiety and depression symptoms that are common in mothers both during pregnancy and postpartum. Methods: 173 mother-child dyads were recruited from the FinnBrain Birth cohort. Maternal psychological stress was measured at 14, 24 and 34 gestational weeks and 3 months, 6 months, 1 year and 2 years after birth. Stress was measured using self-report questionaires on depression and anxiety symptoms. Children underwent MRI scans at 5 years of age. Gray matter, white matter and subcortical gray matter brain volumes were obtained from structural T1-images. Centile scores for volumetric values were calculated using BrainChart. Results: There was an association between maternal anxiety at 3 months postpartum and smaller cortical gray matter volume centile scores at 5 years old. Prenatal or postnatal maternal depression or anxiety symptoms did not associate with subcortical gray matter and white matter Conclusions: This study suggests that the first months after birth are a specifically sensitive time for cortical brain development and maternal psychological stress during this time may affect the development of the brain. In addition, these findings provide support for hypotheses that early life stress exposure might delay or alter the direction of development.